Assessment of pediatric asthma exacerbation with the use of new PROMIS measures. (3rd October 2021) - Nelson, Amanda, Ashima; Singh; Dasgupta, Mahua; Simpson, Pippa M.; Chiu, Asriani; Brousseau, David C.; Panepinto, Julie A.
Abstract: Objective: Patient reported outcome measures, such as the Patient Reported Outcomes Measurement Information System (PROMIS) may be used to assess patient functioning for asthma and aid in understanding the impact of asthma exacerbation. These domains may be utilized as endpoints in clinical trials and to guide clinical care. The purpose of this study was to determine psychometric properties of the new PROMIS measures for children with asthma, at baseline and with exacerbation. Methods: We conducted a cross-sectional analysis of children with acute asthma exacerbation or at baseline health. Psychometric properties of validity (using known groups and correlation) and reliability (using Cronbach's alpha and IRT) for the new PROMIS measures were determined. Results: Our study included 220 subjects, 102 were enrolled during an acute exacerbated state. Cronbach's alpha and IRT reliability was greater or equal to 0.75. Our subjects experiencing an acute exacerbated state reported worse T-scores for pain related domains: pain behavior 45.7 vs 53.5 ( p < 0.001), pain quality sensory 44.4 vs 48.5 ( p < 0.005), pain quality affective 42.5 vs 51.3 ( p < 0.001), and physical stress experience 60.5 vs 65.4 ( p < 0.001); and asthma impact 47.9 vs 61.0 ( p < 0.001), than subjects at baseline. Child and parent-proxy agreement ranged from 35% to 56%. Conclusions: The new Pediatric PROMIS domains are valid and reliable for use in children with asthma, for both child-reported and parent-proxy reported outcomes. It was determined that children with acute asthma exacerbation have worse patient reported outcomes (PROs) for the new pain related domains and asthma impact.